Mannitol in reperfusion skin island flaps injury - Schanaider,Alberto (1999)
In the skin, the concept of reperfusion injury is well established. The application of this knowledge to deal with skin flap surgery problems, has a great prophylactic potential. This experimental study was performed to evaluate the action of mannitol as a scavenger of oxygen-free radicals, after an ischemia-reperfusion injury on skin island flaps. Thirty six male Wistar rats were divided into three test groups (n = 12): a non-ischemic group (group I), and two others (groups II and III) which were subjected to nine hours of ischemia following by 30 minutes of reperfusion. After seven days, all animals of group II, treated with saline, showed full skin flap necrosis. The assessment of group III, that received a 20% solution of mannitol prior to the onset of reperfusion, revealed 75% (9/12) of flap viability. These results suggest that pre-treatment with mannitol is able to enhance flaps survival with significantly less tissue necrosis (p <0.02).